Duplex PCR-ELONA for the detection of pork adulteration in meat products. (30th July 2019) - Skouridou, Vasso; Tomaso, Herbert; Rau, Jörg; Bashammakh, Abdulaziz S.; El-Shahawi, Mohammad S.; Alyoubi, Abdulrahman O.; O'Sullivan, Ciara K.
Highlights: Duplex PCR amplification of pork in beef and chicken products. Tailed primers allow the generation of duplex flanked by single stranded tails. Enzyme-linked oligonucleotide assay for direct detection via hybridisation of PCR products. Sensitivity of 71–188 pg of genomic DNA from each species was achieved. The presence of 0.5–1% pork in binary DNA add-mixtures and in raw meat mixtures could be detected. Abstract: In this work, a duplex PCR–Enzyme Linked Oligonucleotide Assay (ELONA) is reported for the sensitive and reliable detection of pork adulteration in beef and chicken products, two of the most widely consumed meat types in the world. The strategy relies on the use of species-specific tailed primers for duplex amplification and simple dilution of the PCR reactions for direct colorimetric detection via hybridization, eliminating the need for any other post-amplification steps. A high sensitivity was achieved, with as low as 71–188 pg of genomic DNA able to be detected using mixtures of control DNA from each species. The strategy was validated using DNA add-mixtures as well as DNA extracted from raw meat mixtures and 0.5–1% w/w pork could be easily detected when mixed with beef or chicken. The proposed approach is simple, sensitive and cost-effective compared to equivalent commercial kits suitable for detecting adulterant pork levels in meat products.